Search and study of young infrared stellar clusters - Azatyan, N.
The “bricks” of the Galactic disc are giant molecular clouds, which are birthplaces of stellar population. Therefore, there is a genetic connection between young stellar objects (YSOs) and their surrounding Interstellar Medium (ISM). The thesis is devoted to a search for young stellar clusters in the vicinity of IRAS sources and a detailed study of three selected star-forming regions: IRAS 05137+3919, 05168+3634, and 19110+1045, which includes determining the parameters of the ISM based on far-infrared data, the identification and classification of YSOs using color-color and color-magnitude diagrams, the modeling of stellar parameters, and the construction and interpretation of the luminosity functions. It is likely that the three young stellar clusters were formed under different scenarios. The age spread of the IRAS 05137+3919 and IRAS 05168+3634 regions is much larger, and, therefore, we concluded that the stellar population is formed as a result of independent condensations. The age spread of the IRAS clusters’ members in the third region, which is a pair of ultra-compact HII regions (UCHIIs), namely G45.12+0.13 and G45.07+0.13, is small. The small age spread suggests that the clusters may originate from a single triggering event. Moreover, high-mass YSOs were obtained only in the G45.07+0.13 and G45.12+0.13 UCHII regions where the ISM initial density was higher and the star formation proceeded relatively quickly.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture